Is a reduction in brown adipose thermogenesis responsible for the change in core body temperature at menopause? - Aldiss, Peter; Budge, Helen; Symonds, Michael E. (Lippincott, Williams & Wilkins, 2016)
Maintenance of thermal homeostasis within a tight range is regulated not only by a variety of internal and external cues but also by sex and biological age. The major organ responsible for adaptive thermogenesis is brown adipose tissue (BAT) and the recent re-discovery of its presence in adult humans has led to huge interest in the role that it may play in modulating cardiometabolic health. Interestingly, as with maintenance of thermal homeostasis, the total amount and metabolic activity of BAT is modulated by sex and biological age. In this short commentary we discuss the recent finding that core-body temperature is reduced in women post-menopause, a period when excess adiposity and increased risk of cardiometabolic disease is evident and postulate that alterations in sex hormones downregulated the thermogenic activity of BAT cold contribute to this deleterious phenotype.